Predicting Consumer Adoption of Point Of Sale (POS) E-Payment System in Nigeria Using Extended Technology Acceptance Model - Chukwuemezie Okeke, Titus; Chibuike Nwatu and Greg Amaechi Ezeh, Basil (British Journal of Marketing Studies, 2017)
This study is concerned with Predicting Consumer Adoption of Point of Sale (POS) e-Payment System in Nigeria Using Extended Technology Acceptance Model. We extended the TAM by adding two variables: consumer awareness and security of operations to ascertain how they predict the original TAM constructs: PU and PEOU to predict POS adoption. The study was based on a sample of 400 respondents in Awka, Nigeria; of which 234 responded. Questionnaire was the instrument for data collection and was designed with five point likert scale. Four items were used to measure each of the variables. The analysis was done with SEM with the aid of AMOS 23 software. This study has established that PEOU and PU positively and significantly impact POS adoption in Nigeria. It also demonstrated that security impacts PEOU positively and significantly but insignificantly on PU. Consumer awareness (CA) significantly and positively impact PU but impact on PEOU is not significant. The study has implications for research and practice. Further researches should be conducted with further extensions to show the mediation and or moderation impacts of the two variables